Hardy kiwifruit leaves (Actinidia arguta): an extraordinary source of value-added compounds for food industry - Almeida, Diana (2021)
The present study reports for the first time the identification and quantification of phenolic compounds, the antioxidant and antimicrobial activities as well as the in vitro radical scavenging activity and intestinal cell effects of A. arguta leaves extracts. Extractions were carried out under water, water:ethanol (50:50) and ethanol. The highest antioxidant activity were obtained in alcoholic extract (IC50 = 53.95 ± 3.09 μg/mL for DPPH; 6628.42 ± 382.49 µmol/mg dry weight basis for FRAP) while the phenolic profile confirmed by HPLC analysis revealed highest amounts of phenolic acids (hydroxycinnamic acid derivatives) and flavonoids (flavan-3-ol and flavonols derivatives). An excellent scavenging activity against reactive oxygen and nitrogen species were determined for all extracts as well as no adverse effects on Caco-2 and HT29-MTX cells in concentrations below 100 μg/mL and 1000 μg/mL, respectively. These results highlight the potentialities of hardy kiwi leaves valorization.